PENGARUH PROFITABILITAS FIRM SIZE TERHADAP DIVIDEND PAYOUT RATIO DIMODERASI LIKUIDITAS PADA BUMN INDONESIA - Nik Amah; Efa Dwi Prasetyowati (INVENTORY: JURNAL AKUNTANSI, 2019)
The purpose of this study aims to empirically examine the effect of profitability and firm size on the dividend payout ratio with liquidity as a moderating variable. This population, namely the BUMN companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The type of research used is descriptive quantitative. The sampling technique using purposive sampling method. Based on the existing criteria, there were 15 BUMN companies that became the research sample. Data analysis techniques used in this study are multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of this study indicate that profitability does not affect the dividend payout ratio. Firm size affects the dividend payout ratio. Liquidity moderates the effect of profitability on the dividend payout ratio. Liquidity does not moderate the effect of firm size on the dividend payout ratio.Keywords: Dividend Payout Ratio, Liquidity, Profitability and Firm Size